Peningkatan Kapasitas Tenaga Kesehatan melalui Workshop SIPETER dalam Mendukung Transformasi Digital Puskesmas - Yaqutina Marjani Santosa; Alifia Puspaningrum; Nugraha, Nur Budi (Journal Of Computer Science Contributions (JUCOSCO), 2025)
The administrative recording process at Puskesmas (Community Health Centers) is still not optimal. One of the common challenges is that the recording process does not correlate with the measurable monitoring of the Puskesmas' work program achievements. One solution that can be implemented to address this issue is the SIPETER application. SIPETER is a technology-based solution designed to replace manual recording and facilitate the achievement of work programs at Puskesmas. However, the successful adoption of this system depends on the readiness of human resources to master its technical features. Therefore, the process of technology transfer in the implementation of the SIPETER application becomes crucial. For this reason, this article proposes a SIPETER application workshop at Puskesmas Cantigi. The SIPETER workshop model at Puskesmas Cantigi includes: (1) introduction to core features, (2) real case simulations, (3) troubleshooting technical issues, and (4) continuous evaluation through a performance dashboard. This community service activity is expected to assist healthcare workers at Puskesmas Cantigi in promptly conducting recording and reporting. Meanwhile, the head of the Puskesmas can monitor the progress of the implementation of the work programs